The Impact of Fairness on Decision Making - An Analysis of Different Video Experiments - Heike Hennig-Schmidt (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
Experimentally observed deviations of behavior from game theoretic predictions suggest that fairness does influence decision making. Fairness in the sense of equality has become an essential element of economic models aiming at explaining actual behavior (cf. Fehr and Schmidt, 1999; Bolton and Ockenfels, 2000). In this paper I will argue that equality is not the only fairness norm to be taken into account. More equity norms than equality exist, including inequality of payoffs. Since inequitable payoff allocations are advantageous for the one player and disadvantageous for the other, subjects may fall prey to a self-serving bias in their fairness perceptions. Opponents may adhere to different conceptions of fairness making agreement impossible. Using the video method (Hennig-Schmidt, 1999) I further show in a bargaining experiment that behavior is goal-oriented. Fairness criteria based on equity norms guide the formation and adaptation of aspiration levels.
Keywords: C7; C90; C92; 330; experimental economics; video experiments; fairness; equity principle; self-serving bias; aspiration levels; decision making